Segregação sexual do emprego em Portugal no último quarto de século – Agravamento ou abrandamento? - Lina Coelho; Virgínia Ferreira (e-cadernos ces)
This paper started off with the challenge of revisiting an article authored by Virgínia Ferreira in the book Portugal: um retrato singular [Portugal: a singular portrait] (Santos, 1993). In the original paper, statistical data of the mid-1980s showed that Portugal presented some differences in the patterns of participation of women in employment both in relation to the more developed countries of the European Economic Community and the other Southern European countries. Portugal was shown as not pursuing the tendency identified in the literature of an increased rigidity in the sexual division of labor resulting from the increased participation of women in the economic activity. Although the phenomenon of sexual segregation of employment was evident, it was weaker than in other countries. The authors now review the data and arguments then undertaken, and update them. The effects of the steep growth of employment in the care economy and in ICT activities are given special attention.